2018
DOI: 10.1159/000487510
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Complications on Cancer Recurrence Rates: A Literature Review

Abstract: Introduction: The inflammatory response to a post-operative infection can increase the risk of tumour recurrence in cancer through the release of pro-inflammatory mediators. The aim of this study was review the literature to assess the relationship between post-operative complications and cancer recurrence. Methods: We performed a literature review of the mechanism of such an association and looked at evidence in different cancer subtypes. Results: A relationship has been identified for many cancer subtypes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 44 publications
0
57
0
Order By: Relevance
“…On deeper analysis, including qualitative evaluation using the MINORS criteria, it was found that many of these papers lacked a definition of either SSI or anastomotic leakage 60,61 and, most importantly, no relationship between adverse events and oncological outcome was reported. In contrast, it is increasingly being recognized in other fields of oncology, such as breast cancer, that there may be a relationship between infection and cancer recurrence 76 . Surprisingly SSI data have not been included in cancer registries.…”
Section: Discussionmentioning
confidence: 99%
“…On deeper analysis, including qualitative evaluation using the MINORS criteria, it was found that many of these papers lacked a definition of either SSI or anastomotic leakage 60,61 and, most importantly, no relationship between adverse events and oncological outcome was reported. In contrast, it is increasingly being recognized in other fields of oncology, such as breast cancer, that there may be a relationship between infection and cancer recurrence 76 . Surprisingly SSI data have not been included in cancer registries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Presurgical parameters. 2 Anaemia: defined as haemoglobin <11.4 g/dL in females and <13 g/dL in males. 3 Hypoalbuminemia: defined as albumin <3.5 g/dL.…”
Section: Cohort Studymentioning
confidence: 99%
“…Therefore, microvascular reconstruction, as a complex surgical procedure performed in patients often with multiple comorbidities—as in oncological patients—can induce serious postoperative complications. The most frequent ones are healthcare-associated infections (HAIs) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…When combined, these interventions form a bundle. Wound bundles have been shown to exert significant improvements in outcomes in elective surgery [7,10,11]. Reducing SSIs requires a team approach, involving all providers, in every phase of care, with a cumulative additive benefit of each aspect in the bundle.…”
Section: Introductionmentioning
confidence: 99%